Twins - McCann, Paul.; Harding, Peter; Chapman, Christopher, 1966-; Contemporary Art Centre of South Australia (Parkside, S. Aust : Contemporary Art Centre of South Australia, 1998)
At of Katie Moore, Michael Newall, Angela Valamanesh, Dean Whitehorn, Alison Main, Alice Vivian.
Exhibition held 6 - 29 November 1998 at CACSA.
Includes bibliographical references.
Keywords: Art, Australian -- 20th century -- Exhibitions; Art, Australian -- 20th century -- Exhibitions